2014
DOI: 10.1111/1567-1364.12183
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces eubayanusandSaccharomyces uvarumassociated with the fermentation ofAraucaria araucanaseeds in Patagonia

Abstract: Mudai is a traditional fermented beverage, made from the seeds of the Araucaria araucana tree by Mapuche communities. The main goal of the present study was to identify and characterize the yeast microbiota responsible of Mudai fermentation as well as from A. araucana seeds and bark from different locations in Northern Patagonia. Only Hanseniaspora uvarum and a commercial bakery strain of Saccharomyces cerevisiae were isolated from Mudai and all Saccharomyces isolates recovered from A. araucana seed and bark s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 69 publications
0
57
1
2
Order By: Relevance
“…Incubation at 30 °C was applied mainly for Northern Patagonia samples ( N = 88), as well as a few Southern samples resulting in absence of yeast growth. Although previous studies in Patagonia (Libkind et al, ; Rodríguez et al, ) isolated a handful of S. eubayanus and Saccharomyces uvarum strains at 30 °C, the new samples did not yield any isolates. These results are consistent with the fact that S. eubayanus and S. uvarum are cryotolerant species that prefer cold habitats (Libkind et al, ).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Incubation at 30 °C was applied mainly for Northern Patagonia samples ( N = 88), as well as a few Southern samples resulting in absence of yeast growth. Although previous studies in Patagonia (Libkind et al, ; Rodríguez et al, ) isolated a handful of S. eubayanus and Saccharomyces uvarum strains at 30 °C, the new samples did not yield any isolates. These results are consistent with the fact that S. eubayanus and S. uvarum are cryotolerant species that prefer cold habitats (Libkind et al, ).…”
Section: Resultsmentioning
confidence: 70%
“…In recent years, new strains of S. eubayanus have been isolated from North America, Asia and New Zealand, as well as Patagonia (Argentina) (Peris et al, , ; Rodríguez et al, ; Bing et al, ; Gayevskiy and Goddard, ), adding complexity to the phylogeography of this species. Population genomic studies have shown that two main populations with high genetic diversity exist in Patagonia (Patagonia A and Patagonia B/Holarctic, referred here as PA and PB/Hol respectively), as well as two divergent subspecies from Asia (Bing et al, ; Peris et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly given its name, this species has also been isolated from cider (Coton et al ., ), sherry (Esteve‐Zarzoso et al ., ) and wine (Ganga and Martinez, ) fermentations worldwide indicating it is widespread, but the phylogeography of this species is not described. The remaining yeast species identified was K. servazzii and has been found in South America on Araucaria araucana seeds (Rodríguez et al ., ), and been isolated from sourdough (Di Cagno et al ., ) and kimchi (Kobayashi et al ., ) fermentations, as well as on wine grapes in Denmark (Lederer et al ., ). Unsurprisingly given the ethanol selection pressure in the isolation media, all three genera found are known to be Crabtree positive (Hagman et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be either caused by the high sporulation capacity of S. eubayanus [48] that resulted in a spore of C902 mating with S. cerevisiae 59A, or by loss of chromosomes post-hybridization due to chromosome instability and even incompatibility. Examples of the latter are the chromosome III from S. cerevisiae that has high loss frequency [28] and the chromosome XII from S. bayanus being partially incompatible with the S. cerevisiae genome [30].…”
Section: Discussionmentioning
confidence: 99%